KONTRIBUSI IQ (INTELLIGENCE QUOTIENT) DAN EQ (EMOTIONAL QUOTIENT) TERHADAP HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS X SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2011/2012 - Fatimah, Siti; Karyanto, Puguh; Rosyidi, Alvi (Pendidikan Biologi, 2012)
ABSTRACT ? This research is aimed to know relationship between: 1)  IQ (Intelligence Quotient) and cognitive learning achievement  of biology of  first  student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012,  2) EQ  (Emotional Quotient) and cognitive learning achievement  of biology of  first  student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012, 3)  IQ  (Intelligence Quotient),  EQ  (Emotional Quotient), and  cognitive learning achievement  of biology of  first  student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012. This was a correlational research. The population were all of the students first grade of SMA Negeri 7 Surakarta in academic year of 2011/2012.  The sample was taken among 74 samples of student using  simple random  sampling technique.  Documentation technique was used to uncover student?s cognitive learning achievement, while  IQ (Intelligence Quotient) dan EQ  (Emotional Quotient) was measured by using test technique. The obtained data was analysed using linier regression analysis in SPSS 17. The result showed that (1) there is correlation  IQ (Intelligence Quotient) and  cognitive learning achievement  of biology of  first  student?s  grade  of  SMA Negeri 7 Surakarta in academic year of 2011/2012, 2) there is correlation EQ (Emotional Quotient)  and  cognitive learning achievement  of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012,  3) there is correlation both of  IQ  (Intelligence Quotient)  and  EQ  (Emotional Quotient) with cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012.  The  three aforementioned correlation are considered as significant and positive valuable.  In addition  the results  showed that  relative  contribution  of IQ toward cognitive learning achievement in Biology  is 48.6%,  relative  contribution  of EQ toward cognitive learning achievement in Biology is 51.4%, Effective contribution of IQ toward cognitive learning achievement in Biology is 7.63%, effective contribution of EQ toward cognitive learning achievement in Biology  is 8.07%, total effective contribution both of IQ and EQ are15.7% Keywords:  IQ (Intelligence Quotient), EQ (Emotional Quotient),cognitive learning achievement in biology, linier regression analysis